Does ibuprofen affect the expression of alginate genes in pathogenic Pseudomonas aeruginosa strains - Babaei, Nastaran; Rasti, Behnam; Zamani, Hojjatolah (Folia microbiologica, 2022)
Conversion to mucoid form is a crucial step in the pathogenesis of P. aeruginosa in burns and cystic fibrosis (CF) patients. Alginate is considered the major component of biofilm and is highly associated with the formation of mucoid biofilm in this species. Nonsteroid anti-inflammatory drugs (NSAIDs), including ibuprofen, have shown promising antibacterial and antibiofilm potential for bacterial pathogens. In this study, we aimed to evaluate the effect of ibuprofen on the expression of alginate synthetase (alg8), GDP-mannose dehydrogenase (algD), and alginate lyase (algL) genes in multiple drug-resistant (MDR) P. aeruginosa strains. The biofilm formation potential and the expression of alg8, algD, and algL among the bacteria treated with ibuprofen (at sub-inhibitory concentration) were investigated using the crystal violet staining and real-time PCR assays, respectively. The minimum inhibitory concentration of ibuprofen for the studied strains was determined 1024-2048 μg/mL. We observed that ibuprofen was able to reduce bacterial biofilm by 51-77%. Also, the expression of alg8, algD, and algL decreased by 32, 52, and 48%, respectively. The reduction of the genes responsible for alginate synthesis indicates promising antivirulece potential of ibuprofen to combat P. aeruginosa infection, especially in burns and CF patients. Our findings suggest that ibuprofen could be used to reduce the pathogenicity of P. aeruginosa that could be used in combination with antibiotics to treat drug-resistant infections.
Keywords: antibakteriální látky; Cystic Fibrosis; cystická fibróza; ibuprofen; Alginates; Biofilms; Pseudomonas Infections; lidé; algináty; Humans; Ibuprofen; Pseudomonas aeruginosa; Anti-Bacterial Agents; pseudomonádové infekce; biofilmy